Distribution of Yeast Species Isolated from Blood Cultures for a Six Year Period in Turkey: a Multicentre Study - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2020)
Bloodstream infections due to yeast species especially Candida spp. have been reported to be important healthcare associated infections with high mortality and morbidity rates. Candidemia causes prolonged hospital stays as well as increased cost. In order to prevent or treat these life-threatening bloodstream infections successfully, nationwide epidemiological data should be available about the etiological agents of these infections. Multi-centre national epidemiological data on yeast bloodstream infections in Turkey is lacking. A retrospective study was designed and data from six different centres in Turkey between 2011 and 2016 years were gathered and analysed for the distribution and frequency of yeast species in order to assist clinicians in their choice of early and appropriate antifungal therapy. All laboratories used automated blood culture systems for the isolation of blood strains. All the participating centres performed the identification of their own isolates by conventional methods using germ tube test, morphology on corn meal agar with tween 80 and chromogenic media and the identification was confirmed by API 20C AUX, API ID 32C or matrix-assisted laser desorption/ionization time of flight mass spectrophotometry (MALDI-TOF MS) systems. The analysis of the results was performed on the basis of intensive care units (ICUs), other inpatient clinics (OICs) and totally all clinics (ACs). Totally 2547 yeast isolates were determined from six participating centres during six years. According to the total ACs results, Candida albicans was the most prevalent species (43.1%), followed by Candida parapsilosis complex (29.1%), Candida glabrata (10.1%), Candida tropkalis (7.5%), Candida krusei (2.4%) and Candida kefyr (1.6%) and the remaining (6.2%) of them consisted of other yeast species. The distribution of the Candida species did not show statistically significant difference between the years, however the increase of C.parapsilosis complex in 2016 was statistically significant, (p= 0.02). During the study period, totally 1054 yeast isolates were obtained from the ICUs of the centres. C.albicans predominated with 476 (45.2%) isolates and C.parapsilosis complex (28.7%), C.glabrata (10.7%) and C.tropicalis (7.3%) were the other leading species in ICUs. Among 1493 isolates of the OICs of six centres participated in the study, C.albicans was the most prevalent species with 622 (41.7%) isolates. The other frequent species of OICs were C.parapsilosis complex (29.5%), C.glabrata (9.6%) and C.tropicalis (7.6%) resembling ICU results. It can be concluded that C.albicans is still the leading cause of bloodstream infections in the six different centres located in various geographical areas of Turkey.
Keywords: Yeast; epidemiology; blood culture; candidemia; Turkey; INTENSIVE-CARE-UNIT; STREAM INFECTIONS; CANDIDEMIA; EPIDEMIOLOGY; CANDIDAEMIA; NATIONWIDE; TRENDS; RESISTANCE; OUTCOMES